A política de financiamento de uma tecnologia de cuidado. Etnografia do processo de reforma psiquiátrica do Serviço de Saúde Dr. Cândido Ferreira - Sartori, Lecy (Universidade Federal de São Carlos, 2015)
This work analyzes the established funding policy in co-management agreement between the Municipal Health Sector Campinas and the Health Service Dr. Cândido Ferreira (Serviço de Saúde Dr. Cândido Ferreira–SSCF) since 1990. From the professionals‘ speech who works in this institution, I describe how, in the SSCF, making politics is inherent to the clinical practice, the negotiating relationship with that Health Sector, the writing strategies and manufacturing agreement documents. The ethnography was held at the Agreement Monitoring Commission, at the House Commission, at the meeting of the Therapeutic Residential Services‘ Team (Serviço Residencial Terapêutico–SRT) and at one training course of this professionals in this area and at commemorative event of the 20 years of its implementation. The changes arising from the reform process within the psychiatric model, described was based on mnemonic professional‘s speech, and its effects on the life of one resident of SRT, reveals the technical and architectural rearrangements that produced the rehabilitation of the inmates, the Individual Therapeutic Project and to a support network. In SRT, a ―care technology‖ was implemented, drawn from the singularity of users, combining not only psychiatric procedures and knowledge, but also clinical, psychological and geriatric in monitoring interventions (continuous control), monitoring (monitoring the distance) and management in order to govern the conduct and the life project of those. The ―clinic of detail‖, the ―therapeutic management‖ and the ―co-management relationship‖ allows the team to evaluate, calculate and discuss the individual demand, rationalized in data which are recorded in documents and made into parameters that disseminate information between professionals enabling the latter to measure the effectiveness of therapeutic interventions and improve them, plan them and manage the SRT goals. This way of proceeding, that transmutes the information in singular knowledge that subscribe thus into documents and makes them visible to the municipal administrators, justifies funding and authorizes the government practices to the SRT.
The funding policy of a care technology. Ethnography of psychiatric reform process Health Service Dr. Cândido Ferreira
Keywords: Antropologia política; Financiamento de projetos; Saúde mental; Political anthropology; Project finance; Mental health; CIENCIAS HUMANAS::ANTROPOLOGIA